Antigen-Presenting Cells in Food Tolerance and Allergy - Liu, Elise G.; Yin, Xiangyun; Swaminathan, Anush; Eisenbarth, Stephanie C. (Frontiers in Immunology, 2021)
Food allergy now affects 6-8% of children in the Western world; despite this, we understand little about why certain people become sensitized to food allergens. The dominant form of food allergy is mediated by food-specific immunoglobulin E (IgE) antibodies, which can cause a variety of symptoms, including life-threatening anaphylaxis. A central step in this immune response to food antigens that differentiates tolerance from allergy is the initial priming of T cells by antigen-presenting cells (APCs), primarily different types of dendritic cells (DCs). DCs, along with monocyte and macrophage populations, dictate oral tolerance versus allergy by shaping the T cell and subsequent B cell antibody response. A growing body of literature has shed light on the conditions under which antigen presentation occurs and how different types of T cell responses are induced by different APCs. We will review APC subsets in the gut and discuss mechanisms of APC-induced oral tolerance versus allergy to food identified using mouse models and patient samples.